Comparing Expert Driving Behavior in Real World and Simulator Contexts - Hiran B. Ekanayake; Per Backlund; Tom Ziemke; Robert Ramberg; Kamalanath P. Hewagamage; Mikael Lebram (International Journal of Computer Games Technology)
Computer games are increasingly used for purposes beyond mere entertainment, and current hi-tech simulators can provide quite, naturalistic contexts for purposes such as traffic education. One of the critical concerns in this area is the validity or transferability of acquired skills from a simulator to the real world context. In this paper, we present our work in which we compared driving in the real world with that in the simulator at two levels, that is, by using performance measures alone, and by combining psychophysiological measures with performance measures. For our study, we gathered data using questionnaires as well as by logging vehicle dynamics, environmental conditions, video data, and users' psychophysiological measurements. For the analysis, we used several novel approaches such as scatter plots to visualize driving tasks of different contexts and to obtain vigilance estimators from electroencephalographic (EEG) data in order to obtain important results about the differences between the driving in the two contexts. Our belief is that both experimental procedures and findings of our experiment are very important to the field of serious games concerning how to evaluate the fitness of driving simulators and measure driving performance.